1978
DOI: 10.1128/jcm.8.3.320-325.1978
|View full text |Cite
|
Sign up to set email alerts
|

Primary isolation media for Legionnaires disease bacterium

Abstract: Yolk sac suspensions infected with the Legionnaires disease bacterium (LDB) were plated onto 17 different bacteriological agar media. The LDB grew only on Mueller-Hinton agar supplemented with 1% Iso Vitale X and 1% hemoglobin (MH-IH). This medium was subsequently analyzed to determine the components required to support growth of the LDB. L-Cysteine hydrochloride can replace the Iso Vitale X reagent, and soluble ferric pyrophosphate can replace hemoglobin. A new medium, F-G agar, was formulated incorporating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1980
1980
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…The first published article to report Legionella growth inhibition under anaerobic conditions was by Feeley et al in 1978. The authors reported that stock cultures of Legionella growth on artificial media (agar) was decreased with each reduction in O 2 and failed to grow under anaerobic conditions [11].…”
Section: Discussion Of Published Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The first published article to report Legionella growth inhibition under anaerobic conditions was by Feeley et al in 1978. The authors reported that stock cultures of Legionella growth on artificial media (agar) was decreased with each reduction in O 2 and failed to grow under anaerobic conditions [11].…”
Section: Discussion Of Published Studiesmentioning
confidence: 99%
“…Building water systems that contain adequate levels of dissolved oxygen can support Legionella cellular respiration, metabolism, and growth, whereas Legionella and other aerobic pathogens are not typically found in anoxic groundwater deep below the water table that has no contact with the atmosphere [13]. Along with other obligate aerobic bacteria Legionella growth is inhibited when DO is too low to support metabolic respiration, making it a critical factor in Legionella's growth [11,12,[14][15][16]. Reducing DO levels in building water systems could be a potential control mechanism in addition to currently recognized methods.…”
Section: Introductionmentioning
confidence: 99%
“…Typical Legionella colonies were subcultured to BCYE with and without l -cysteine. Biochemical tests, including autofluorescence, catalase, oxidase, urease, gelatinase, and browning on Feeley Gorman agar ( 29 , 30 ), were performed. A step of acid washing with 0.2 mol/liter HCl-KCl, pH 2.2, for 3 min ( 12 , 31 ) or heat treatment at 50°C for 10 min ( 32 ) and an additional plating on BCYE medium with glycine, vancomycin, polymyxin B, and dyes were used for more difficult samples in which bacterial overgrowth was found.…”
Section: Methodsmentioning
confidence: 99%
“…Die beiden Stoffe erwiesen sich als essentiell fur das Legionellenwachstum und werden seither in fast allen flussigen und festen Nahrmedien verwendet. Die Entwicklung ftihrte zum Feeley-Gorman-Agar, der die Bildung eines braunen Pigments und im langwelligen UV -Licht fluoreszierende Legionellenkolonien be-G. Ruckdesche1 und W. Ehret giinstigt [176]. Braunes Pigment wird vor aHem auf Medien produziert, die mit Phenylalanin oder Tyrosin angereichert sind [17].…”
Section: Kuiturunclassified